Green synthesis of silver nanoparticles from seed extract of Brassica nigra and its antibacterial activity - RAKHSA PANDIT (Smujo International, 2015)
Abstract. Pandit R. 2015. Green synthesis of silver nanoparticles from seed extract of Brassica nigra and its antibacterial activity. Nusantara Bioscience 7: 15-19. We report the green synthesis of silver nanoparticles using seed extract of Brassica nigra. UV-visible spectroscopic analysis showed the absorbance peak at 432 nm which indicated the synthesis of silver nanoparticles. Nanoparticles Tracking and Analysis (NTA) was used to determine the size of synthesized silver nanoparticles. Zeta potential analysis was carried out to study the stability of nanoparticles while FTIR analysis confirmed the presence of proteins as capping agents that provided stability to nanoparticles in colloid. Antibacterial activity of silver nanoparticles was evaluated against Propionibacterium acnes, Pseudomonas aeruginosa, and Klebsiella pneumoniae. The activity of Vancomycin was significantly increased in combination with silver nanoparticles showing synergistic activity against all bacteria while the maximum activity was noted against P. acnes.